A.m. p.m. yoga for beginners [videorecording (DVD)] - Wohl, Michael; Benagh, Barbara; Bstan- dzin-rgya-mtsho, Dalai Lama XIV, 1935- (Bodywisdom Media ; Distributed by Vivendi Visual Entertainment, 2007)
A wide variety of yoga routines for beginning and ending the day.